A Bent Fiber Optic with a D-Shaped Structure for Temperature Sensing - Sulaiman, Nazrah Ilyana; Ngajikin, Nor Hafizah; Che Abd Rashid, Nurfatihah; Md Yassin, Muhammad Zakir; Ali, Siti Hajar Aminah; Yaacob, Maslina; Cholan, Noran Azizan (International Journal of Integrated Engineering, 2026)
A simple and cost-effective plastic optical fiber temperature sensor is demonstrated in this paper. This paper presents the development of a bent fiber optic with a D-shaped structure. A D-shape region on the plastic optical fibre (POF) is created by side-polishing the surface of the POF until a curve D-region is formed, thereby exposing part of the fiber’s core and cladding. This exposed region enables the surrounding temperature to directly interact with the propagating light within the POF, influencing its intensity. To enhance the sensitivity, the POF sensor is further bent to induce a macro bending effect. Based on the experimental results, the sensor exhibits a linear response to temperature ranging from 30 °C to 80 °C. In addition, the highest sensitivity value achieved is 1.5 x 10-3 , obtained with a D-region of 1 cm at a wavelength of 778 nm. This proposed sensor demonstrates high sensitivity and linearity compared to previous developments.